Hadis Tentang Eksistensi Allah SWT - Siregar, Idris (SHAHIH (Jurnal Ilmu Kewahyuan), 2023)
Efforts to prove the existence of God is an important endeavor, not only to convince other people (read: atheists and agnostics) that God exists rationally, but also to pave the way for claims to the truth of revelation, if the arguments are strong. However, efforts to prove the existence of God through philosophy are also not without risk, because if that effort fails, in the sense that it does not have strong and irrefutable arguments, then it becomes a reason for an atheist or agnostic to stick to his stance: not believing in the existence of God. The hadith about the existence/form of Allah SWT after being studied and traced from the path of Imam Bukhari and Ahmad is sourced from Imran bin Husein with continued sanad and tsiqqah, starting from the initial sanad to the end of the sanad. Likewise from the point of view of the matan it also looks authentic because there is no apparent conflict with the Qur'an. In understanding this hadith, the form of Allah SWT described in the hadith is monotheism and the beginning and the end.